RANS-VOF modelling of the hydraulic performance of the LOWREB caisson - Iván López (2018)
The LOWREB caisson is an innovative multi-chambered, low-reflection structure that incorporates inner weirs at each dissipative chamber to promote wave energy dissipation. It was designed to be applied either as external caisson breakwater or as low reflection quay-wall. In this paper, the OpenFOAM (R) CFD numerical package was used to implement a RANS-VOF numerical model of the LOWREB caisson concept, which was then validated using results from experimental tests in a two-step approach: qualitatively, by comparing the "wave-structure" interaction on both physical and numerical models, and quantitatively, by comparing the reflection coefficients determined from the results of the numerical model simulations and those from the physical model tests. Once validated, the numerical model was used to carry out a comprehensive study of the hydrodynamic behavior of the LOWREB caisson aiming the understanding of the wave energy dissipation mechanisms and the assessment of its hydraulic efficiency with respect to wave reflection under an extended range of hydrodynamic conditions (e.g., water levels, wave heights, and wave periods). The numerical study confirmed the importance of the inner weirs on the wave energy dissipation. The hydraulic efficiency of the LOWREB caisson was found to be highly influenced by the combined effect of the wave period and water level. However, the influence of the wave height is not negligible: in general, energy dissipation increases with the wave height. Overall, the LOWREB caisson presents its best performance for the high and mean water level conditions, with all the values of the reflection coefficient below 70% and most of them in the range 30%-60%. The worse results obtained for the lower water level were attributed to the difficulties that waves have to overtop the weirs and enter the dissipative chambers, for this water level. In addition, streamlines, velocity and vorticity fields enabled obtaining important insights on the wave energy dissipation processes that take place during the wave-structure interaction, which results in the development of several vortices, not only inside the dissipative chambers, but also in front of the structure.